Liquid Biopsy in Organ Damage: small extracellular vesicle chip-based assessment of polytrauma - Wang, Bingduo; Wöhler, Aliona; Greven, Johannes; Salzmann, Rebekka J. S.; Keller, Cindy M.; Tertel, Tobias; Zhao, Qun; Mert, Ümit; Horst, Klemens; Lupu, Ludmila; Huber-Lang, Markus; van Griensven, Martijn; et al. (Frontiers in Immunology, 2023)
Background Despite major advances in medicine, blood-borne biomarkers are urgently needed to support decision-making, including polytrauma. Here, we assessed serum-derived extracellular vesicles (EVs) as potential decision-makers in polytrauma. Objective Our Liquid Biopsy in Organ Damage (LiBOD) study aimed to differentiate polytrauma with organ injury from polytrauma without organ injury. Through our analysis of blood-borne small EVs at an individual level using a combination of immunocapture and high-resolution imaging. Methods To this end, we isolated, purified, and characterized small extracellular vesicles (EVs) according to the latest MISEV guidelines from human blood collected within 24hrs post-trauma, and validated our results using a porcine polytrauma model. Results We found that small EVs derived from monocytes CD14+ and CD14+CD61+ were significantly elevated in polytrauma with organ damage. Precisely, our findings revealed that CD9+CD14+ and CD14+CD61+ small EVs exhibited superior performance compared to CD9+CD61+ small EVs in accuracy indicating polytrauma with organ damage reaching a sensitivity and specificity of 0.81% and 0.97%, respectively. The results in humans were confirmed in an independent porcine model with polytrauma. Conclusions This finding suggests that these specific types of small EVs may serve as valuable non-invasive and objective biomarker for assessing and monitoring the severity of polytrauma and associated organ damage.